2021
DOI: 10.17645/mac.v9i2.3824
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Eudaimonic Experience’: A Scoping Review of the Concept in Digital Games Research

Abstract: Digital games have evolved into a medium that moves beyond basic toys for distraction and pleasure towards platforms capable of and effective at instigating more serious, emotional, and intrapersonal experiences. Along with this evolution, games research has also started to consider more deeply affective and cognitive reactions that resemble the broad notion of eudaimonia, with work already being done in communication studies and media psychology as well as in human–computer interaction. These studies offer a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 60 publications
1
66
0
1
Order By: Relevance
“…Characteristic items for assessing appreciation are 'being touched,' 'being moved,' 'tender,' and 'poignant' (Oliver et al, 2018). Appreciation can be induced by movies (Wirth, Hofer, & Schramm, 2012), textual narratives (Lewis, Tamborini, & Weber, 2014), social media (Dale et al, 2020;Ji et al, 2019;Rieger & Klimmt, 2019), and by playing video games (Daneels et al, 2021). Episodes of appreciation are associated with reduced prejudice (Bartsch, Oliver, Nitsch, & Scherr, 2016;Oliver et al, 2015) and with motivation for personal growth (Bartsch, Kalch, & Oliver, 2014;Oliver & Bartsch, 2011).…”
Section: Appreciationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic items for assessing appreciation are 'being touched,' 'being moved,' 'tender,' and 'poignant' (Oliver et al, 2018). Appreciation can be induced by movies (Wirth, Hofer, & Schramm, 2012), textual narratives (Lewis, Tamborini, & Weber, 2014), social media (Dale et al, 2020;Ji et al, 2019;Rieger & Klimmt, 2019), and by playing video games (Daneels et al, 2021). Episodes of appreciation are associated with reduced prejudice (Bartsch, Oliver, Nitsch, & Scherr, 2016;Oliver et al, 2015) and with motivation for personal growth (Bartsch, Kalch, & Oliver, 2014;Oliver & Bartsch, 2011).…”
Section: Appreciationmentioning
confidence: 99%
“…More recent research explains these phenomena via eudaimonic motivation: Striving for "greater insight, self-reflection, or contemplations of poignancy or meaningfulness (e.g., what makes life valuable)" (Oliver, 2008, p. 42). Recent research reveals that eudaimonic themes are prevalent not only in movies and Facebook posts (Dale et al, 2020;Dale, Raney, Janicke, Sanders, & Oliver, 2017) as well as digital games (Daneels, Bowman, Possler, & Mekler, 2021), but also in extremist propaganda (Frischlich, 2020;Frischlich, Rieger, Morten, & Bente, 2018). Accordingly, responses to these eudaimonic themes are relevant for the motivation to enhance others' well-being (Freeman, Aquino, & McFerran, 2009) but also for attraction to extremist groups (Frischlich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work showed that active indexing can foster understanding and meaningful relationships [16,41,91]. Particularly in educational history [34,72] and video game research [19,37,74], findings report on greater learning effects and understanding when the content addressed participants' emotions, for which moral dilemmas are already used. However, considering the process of fostering meaningful user-place relationships, HCI research is still limited regarding strategies in general [3,80], including the role of active indexing and the influence of user's emotion in this context.…”
Section: Discussionmentioning
confidence: 99%
“…A widely used strategy to create a strong emotional effect for video game players is moral dilemmas. According to prior work, they increase player engagement and evoke meaningful playing experiences [19,37,74]. In Iten et al [44], authors explored decisionmaking characteristics to create meaningful player experiences.…”
Section: Moral Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation